2015
DOI: 10.3346/jkms.2015.30.s1.s81
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in the Incidence of Bronchopulmonary Dysplasia among Very-Low-Birth-Weight Infants in Korea

Abstract: We investigated the incidence of bronchopulmonary dysplasia (BPD) in very-low-birth-weight (VLBW) infants in Korea using the Korean Neonatal Network (KNN) data. In total, 2,386 VLBW infants born from January 2013 to June 2014 were prospectively registered. BPD was defined as supplemental oxygen or positive pressure support at 36 weeks postmenstrual age (PMA). The overall incidence of BPD was 28.9%, and the overall mortality rate in the neonatal intensive care units (NICUs) was 11.9%. To investigate recent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
2
18
1
1
Order By: Relevance
“…The conflict in results regarding to the effect of CLD and respiratory treatments on development of IH could be attributed to higher ratios of those variables in that studies when compared with our study population; which is also higher than the recent literature. 15 A noteworthy finding in our study is that RDS and reaching to full enteral feeding after 10 days were found to have a predictive value in IH development. Previously, early respiratory problems were linked to IH in two studies.…”
Section: Discussionsupporting
confidence: 62%
“…The conflict in results regarding to the effect of CLD and respiratory treatments on development of IH could be attributed to higher ratios of those variables in that studies when compared with our study population; which is also higher than the recent literature. 15 A noteworthy finding in our study is that RDS and reaching to full enteral feeding after 10 days were found to have a predictive value in IH development. Previously, early respiratory problems were linked to IH in two studies.…”
Section: Discussionsupporting
confidence: 62%
“…The time on endotracheal ventilation in this present study was relatively shorter compared to those reported in previous studies 6,12) . According to the latest nationwide survey 35) , the combined rates of BPD or death were 68.7% at 25 weeks GA and 58.9% at 26 weeks GA. In the present study, the combined rate of clinical BPD or death was about 40%.…”
Section: Discussionmentioning
confidence: 99%
“…15,29 Furthermore, other conditions contribute to the establishment of a poor prognosis such as bronchodysplasia, including newborns weighting less than 1,000 g, Apgar test performed at the 5 th minute of their life and acute pulmonary diseases. 30 Newborns showing signs of respiratory discomfort tends to require immediate resuscitation as well as respiratory support, 11 in which the lower the GA the greater the possibility of using positive pressure ventilation. 13 In addition, the death rates among newborns increase in the presence of endotracheal intubation and the time required for them to undergo mechanical ventilation.…”
Section: Interventions That Influence the Prognosis Of Newbornsmentioning
confidence: 99%